2004
DOI: 10.1016/j.jcrs.2004.04.050
|View full text |Cite
|
Sign up to set email alerts
|

Artisan lens implantation to correct aphakia after vitrectomy for retained nuclear lens fragments

Abstract: After the removal of dislocated lens fragments with a PPV, Artisan IOL implantation in aphakic patients without capsule support led to few complications and good visual acuity. Placement of an Artisan IOL requires fewer manipulations than transscleral suture fixation of a posterior chamber IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 36 publications
0
25
1
Order By: Relevance
“…Severe hyperopia developed in only one eye. However, postoperative refractive error was more than previous reports of either Artisan IOL 1,7,12 or iris fixated PCIOL. 13 One reason might be inaccurate keratometry in most of our cases due to irregular astigmatism caused by previous repaired corneoscleral laceration.…”
Section: Complicationscontrasting
confidence: 59%
See 3 more Smart Citations
“…Severe hyperopia developed in only one eye. However, postoperative refractive error was more than previous reports of either Artisan IOL 1,7,12 or iris fixated PCIOL. 13 One reason might be inaccurate keratometry in most of our cases due to irregular astigmatism caused by previous repaired corneoscleral laceration.…”
Section: Complicationscontrasting
confidence: 59%
“…Except The Artisan IOL have been used safely for secondary implantation in adults and children with aphakia. 1,7,[9][10][11][12] They have also been used after traumatic injuries to the globe. [9][10][11][12] Gü ell et al 7 reported satisfactory results of Artisan IOL implantations in 16 aphakic patients.…”
Section: Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Since retinal detachment is a common and sight-threatening complication in these eyes, Moore et al 16 report in detail the incidence and clinical course of eyes with retinal detachment following PPV for retained lens fragments in a large consecutive series. In view of the fact that CME is also a common sight-threatening complication in these eyes, we studied the incidence and clinical course of eyes with CME following PPV for retained lens fragments in a large consecutive series.…”
mentioning
confidence: 99%